Examining Examples and Elements of Illegal Competition and Anti-Competitive Practices with an Emphasis on the Resulting Civil Liability - Leila Ghaemi; Hossein Ghorbanian; Alireza Hasani (پژوهشهای حقوقی)
One of the goals of the legal and jurisprudential system is orders for prosperous and competitive business, so that sellers and producers receive real wages and buyers receive the best quality by paying the minimum price, applying illegal competition and using anti-competitive procedures. It is one of the strategies that some economic companies use to remove competitors from the market. In this research, first the examples and elements of these acts and then the civil responsibility resulting from them are examined. Finally, it was found that articles 249 and 244 of the General Penalty Law deal with issues related to illegal competition, anti-competitive practices, and especially the concepts of insidious competition, and specify the civil and legal responsibilities related to these actions. which is not subject to penal regulations, the injured party can request compensation for material and moral damages according to the civil liability law, and in fraudulent competition, in addition to requesting compensation, the aggrieved person can request to prevent and stop actions that are included in the definition of fraudulent competition. Please ask the court, taking into account new and creative ways of applying anti-competitive procedures and conducting insidious competition, the need for more legal supervision and the establishment of new laws in accordance with the civil responsibility of applying new procedures and illegal competition, especially in cyberspace and according to With the progress of science, it is felt more and more.